ANALYSIS OF THE FACTORS OF CONVENIENCE, PRICE, AND QUALITY OF SHOPEE APPLICATION ACCEPTANCE SERVICES FOR STUDENTS OF THE BAKTI NUSANTARA INSTITUTE USING THE TAM MODEL - Fauzi Fauzi; Miswan Gumanti; Muhamad Muslihudin (JMBI (Journal of Marketing and Business Intelligence), 2026)
This study aims to analyze the influence of perceived ease of use, price perception, and service quality on the acceptance of the Shopee application among students of Institut Bakti Nusantara using the Technology Acceptance Model approach with SEM-PLS. This research employs a quantitative method with data collected through questionnaires from 103 respondents consisting of second, fourth, and sixth semester students. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships among variables. The results indicate that perceived ease of use, price perception, and service quality have a positive and significant effect on application acceptance, both partially and simultaneously. Service quality is identified as the most dominant factor, followed by perceived ease of use and price. The coefficient of determination (R²) of 0.72 indicates a strong predictive capability of the model. This study contributes theoretically to the extension of TAM by incorporating relevant external variables in the e-commerce context and provides practical implications for digital platform providers to enhance service quality, usability, and competitive pricing strategies.